(untitled) (African Journal of Biomedical Research, 2024)
Urinary tract infections (UTI) affect the structures involved in the secretion and elimination of urine. It is a common health concern and contributes about 13-33% of infection in pregnancy. The prevalence of UTI among pregnant women attending antenatal clinic in Iyi-Enu mission hospital and the sensitivity of isolates recovered, to antibiotics was studied. A total of 120 midstream urine samples collected from pregnant women who consented to the study, between January and March, 2023, were cultured on MacConkey agar, Blood agar and Cystine Electrolyte Deficient Agar. Isolates were identified using colony morphology, Gram stain reaction and biochemical tests. Susceptibility of the isolates to antibiotics was determined using Kirby-Bauer disc diffusion method. Results obtained from the structured questionnaire used for demographic data were statistically analyzed. The prevalence of UTI among pregnant women was 24.2%. The isolates recovered include; Escherichia coli (24.1%), Klebsiella spp. (18.5%), Proteus mirabilis (7.4%), Pseudomonas spp. (5.6%) and Staphylococcus aureus (44.4%). Gram negative bacteria were most susceptible to Cefuroxine (63%) and resistant to Ceftazidine (80.7%). Gram positive isolates were susceptible to Levofloxacin (100%) but resistant to Amoxicillin (83.3%). Both Gram negative and Gram positive organisms were recovered from UTI of pregnant women and were found to be sensitive to Cefuroxine and Levofloxacin respectively. There is need for proper diagnosis of UTI before treatment to avoid resistance of uropathogens to antibiotics.